2022
DOI: 10.1111/jbi.14353
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term monitoring in endangered woodlands shows effects of multi‐scale drivers on bird occupancy

Abstract: Aims The effect of spatial scale on the location and abundance of species has long been a major topic of interest in ecology. Accounting for key drivers at multiple scales is critical for rigorous description of patterns of species distribution and biodiversity change. We quantified the effects of potential drivers of bird occupancy across a geographically dispersed, but heavily disturbed and fragmented ecosystem. Location Threatened Box‐Gum Grassy Woodlands in south‐eastern Australia, which stretch across 9° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…Small passerines (<60 g) are excluded from the sites that they occupy and only large‐bodied species remain in the presence of these strong interactors (Kutt et al, 2016; Thomson et al, 2015). It suggests that the presence of miners acts as a sieve and the composition of bird assemblages is homogenized where they occur (Hingee et al, 2022). In turn, these results evince that it is not straightforward to differentiate between patterns arising from environmental filtering processes from those arising from species interactions since, in some circumstances, the existence of strong competition (widespread community‐level displacement) generates an imprint similar to that expected if the environment exerts an overwhelming influence on community assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Small passerines (<60 g) are excluded from the sites that they occupy and only large‐bodied species remain in the presence of these strong interactors (Kutt et al, 2016; Thomson et al, 2015). It suggests that the presence of miners acts as a sieve and the composition of bird assemblages is homogenized where they occur (Hingee et al, 2022). In turn, these results evince that it is not straightforward to differentiate between patterns arising from environmental filtering processes from those arising from species interactions since, in some circumstances, the existence of strong competition (widespread community‐level displacement) generates an imprint similar to that expected if the environment exerts an overwhelming influence on community assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them exert a negative influence on other species which end up being extirpated from the area. In turn, these winner species can interact positively as recent studies have reported (Hingee et al, 2022;Westgate et al, 2021). However, these positive associations may merely reflect shared ecological preferences and/or indirect effects.…”
Section: Species Pair Strength (Mean [Range])mentioning
confidence: 98%
“…Our method for selecting environmental predictors of species occupancy followed Hingee et al . (2022) and is the topic of the Supporting Information (Appendix ). The model passed a number of diagnostic tests (Section 5.5 of Appendix : Model fitting and selection), suggesting that estimates of occupancy probability, and estimated uncertainty of these estimates, can be trusted when the modelling assumptions are satisfied.…”
Section: A Joint‐species Statistical Modelmentioning
confidence: 99%
“…The model accounted for interspecies correlation and imperfect detection (Tobler et al 2019). Our method for selecting environmental predictors of species occupancy followed Hingee et al (2022) and is the topic of the Supporting Information (Appendix S1-S3). The model passed a number of diagnostic tests (Section 5.5 of Appendix S1: Model fitting and selection), suggesting that estimates of occupancy probability, and estimated uncertainty of these estimates, can be trusted when the modelling Major site-scale predictors of species occupancy were the presence of the hyper-aggressive native honeyeater, the Noisy Miner (Manorina melanocephala), and whether the woodland area was planted versus remnant.…”
Section: A Joint-species Statistical Modelmentioning
confidence: 99%